Termination of the contract for service in the National Police of Ukraine - Vereitin, S. V.; Вереітін, С. В. (Legal, Economic Science and Praxis. - 2023. - № 8. - P. 46-50, 2023)
У статті досліджено особливості припинення контракту про проходження служби в Національній поліції України. Зазначено, що служба в Національній поліції України є надзвичайно специфічним і відповідальним видом трудової діяльності. Це передбачає наявність спеціального правового регулювання трудових відносин поліцейських, яке встановлює, зокрема, особливості прийому до служби в поліції та звільнення з неї. Надано пропозиції та рекомендації щодо вдосконалення теоретичних положень трудового права щодо визначення особливостей припинення контракту про проходження служби в Національній поліції України та відповідних норм загального та спеціального трудового законодавства.

The article examines the specifics of termination of the contract for service in the National Police of Ukraine. It is indicated that service in the National Police of Ukraine is an extremely specific and responsible type of labor activity. This presupposes the existence of a special legal regulation of labor relations of police officers, which establishes, in particular, the specifics of admission to police service and dismissal from it. The purpose of the article is to provide proposals and recommendations for improving the theoretical provisions of labor law regarding the determination of the specifics of the termination of the contract for service in the National Police of Ukraine and the corresponding norms of general and special labor legislation. The tasks of the article are to study the points of view of scientists regarding the general principles of termination of the employment contract, as well as to reveal the specifics of the termination of the contract of service in the National Police of Ukraine. It is noted that the contract, unlike an ordinary employment contract, can be terminated on the grounds provided for in it, in view of this, it is justified that the termination of the contract should be understood as the termination of the employment relationship on all the grounds provided for in the labor legislation and in the contract itself. The expediency of supplementing Clause 2 of Chapter VI of the Standard Form of the Contract on Police Service: Subclause 4) with the following content: "in connection with the disclosure by Party 2 of official information that led to a violation of citizens' rights", Subclause 5) with the following content: "in connection with the actions of Party 2, which caused a negative public response and lowering the authority of the National Police of Ukraine", sub-item 6) with the following content: "in connection with the infliction by Party 2 of significant material damage to the National Police of Ukraine", sub-item 7 ) with the following content: "in connection with the systematic non-fulfillment by the Party of 2 indicators of official activity."

В статье исследованы особенности прекращения контракта о прохождении службы в Национальной полиции Украины. Отмечено, что служба в Национальной полиции Украины является чрезвычайно специфическим и ответственным видом трудовой деятельности. Это предполагает наличие специального правового регулирования трудовых отношений полицейских, устанавливающего, в частности, особенности приема в службу в полиции и освобождения от нее. Даны предложения и рекомендации по усовершенствованию теоретических положений трудового права по определению особенностей прекращения контракта о прохождении службы в Национальной полиции Украины и соответствующих норм общего и специального трудового законодательства.
Keywords: працівник; роботодавець; поліцейський; контракт; трудовий договір; правове регулювання; трудові відносини; employee; employer; police officer; contract; employment contract; legal regulation; labor relations; работник; работодатель; сотрудник полиции; трудовой договор; правовое регулирование; трудовые отношения